2021
DOI: 10.18231/j.ijcap.2021.052
|View full text |Cite
|
Sign up to set email alerts
|

Study of QT interval prolongation in asymptomatic type-2 diabetes mellitus patients with and without microalbuninuria

Abstract: QT interval abnormalities are the best predictors of cardiovascular deaths. Microalbuminuria is an independent marker for cardiovascular disease in diabetes mellitus. Hence QT interval abnormalities in diabetics with or without microalbuminuria were evaluated in this study. To study QT interval abnormalities in asymptomatic type 2 diabetic patients with or without microalbuminuria. : Open label controlled study with 214 subjects of either sex. Group A healthy subjects (n=100), group B asymptomatic, type 2 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The abovementioned literature supports the association of corrected QT interval prolongation with microalbuminuria in type 2 diabetes patients. However, different findings were reported in a study by Mustafa in 2021 and have not found a significant association between the corrected QT interval and diabetic patients with microalbuminuria [ 28 ].…”
Section: Discussionmentioning
confidence: 81%
“…The abovementioned literature supports the association of corrected QT interval prolongation with microalbuminuria in type 2 diabetes patients. However, different findings were reported in a study by Mustafa in 2021 and have not found a significant association between the corrected QT interval and diabetic patients with microalbuminuria [ 28 ].…”
Section: Discussionmentioning
confidence: 81%